2015
DOI: 10.7567/apex.8.073009
|View full text |Cite
|
Sign up to set email alerts
|

Spin pumping blocked by single-layer graphene

Abstract: We demonstrate that spin pumping in a Ni 81 Fe 19 /Pt bilayer is strongly suppressed by inserting single-layer graphene (SLG) at the interface. Spin pumping in the Ni 81 Fe 19 /Pt bilayer enhances the magnetization damping of the ferromagnetic layer, which is quantified from the microwave frequency dependence of the ferromagnetic resonance linewidth. We show that the enhancement of the magnetization damping due to spin pumping disappears in a Ni 81 Fe 19 /SLG/Pt trilayer. This result indicates that spin pumpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As discussed above, measured V LSSE originates from J s, which is generated in the YIG layer. Injected J s from the YIG layer can be expressed as , where g ↑↓ is the spin mixing conductance, and m is the magnetization unit vector. Thus, spin mixing conductance and magnetization have important influence on J s transport from the ferromagnetic layer (e.g., YIG) to the detection layer (e.g., Pt).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, measured V LSSE originates from J s, which is generated in the YIG layer. Injected J s from the YIG layer can be expressed as , where g ↑↓ is the spin mixing conductance, and m is the magnetization unit vector. Thus, spin mixing conductance and magnetization have important influence on J s transport from the ferromagnetic layer (e.g., YIG) to the detection layer (e.g., Pt).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, spin mixing conductance and magnetization have important influence on J s transport from the ferromagnetic layer (e.g., YIG) to the detection layer (e.g., Pt). Pt/GR/YIG structures have smaller reported g ↑↓ than Pt/YIG structures, implying that graphene interlayers block spin injection from the YIG layer. ,, Park et al, for example, reported that g ↑↓ reduced from ∼6.12 × 10 17 to ∼1.09 × 10 17 m –2 by inserting SL-GR between Pt and YIG. This g ↑↓ reduction for Pt/GR/YIG continues with increasing GR thickness because spin pumping exponentially decays with increasing barrier thickness in the Pt/barrier/YIG trilayer…”
Section: Resultsmentioning
confidence: 99%